Synchronous melanomas arising within nevus spilus - Brito,Maria Helena Toda Sanches de (2017)
Abstract: Nevus spilus is a melanocytic cutaneous lesion consisting of a light brown background macule with numerous superimposed darker maculopapular speckles. Melanoma arising from a nevus spilus is rare, with less than 40 cases reported to date. The absolute risk for malignant transformation is not well defined, lacking a standardized management approach. We report a new case of melanoma arising from nevus spilus, with the additional peculiarity of multifocality. We offer our recommendations for the management of the condition.